2014
DOI: 10.1111/idh.12098
|View full text |Cite
|
Sign up to set email alerts
|

The influence of educational level and oral hygiene behaviours on DMFT index and CPITN index in an adult Italian population: an epidemiological study

Abstract: The oral health status, in terms of periodontal disease and dental caries, appears correlated with patients' educational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 28 publications
7
35
2
13
Order By: Relevance
“…Ospina et al 8 identified schooling as the variable with greater strength of association with oral hygiene in a sample of the general population in Colombia. In the CPS group, schooling correlated positively with flossing, which is consistent with data reported by Vano et al 5 in Italian adult patients, in whose oral hygiene habits were better at higher educational levels. In the present study, belonging to medium-low socioeconomic stratum was associated with poor oral hygiene habits in GPS and CPS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Ospina et al 8 identified schooling as the variable with greater strength of association with oral hygiene in a sample of the general population in Colombia. In the CPS group, schooling correlated positively with flossing, which is consistent with data reported by Vano et al 5 in Italian adult patients, in whose oral hygiene habits were better at higher educational levels. In the present study, belonging to medium-low socioeconomic stratum was associated with poor oral hygiene habits in GPS and CPS.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, belonging to a medium-high or high socioeconomic stratum was associated with better habits. Furthermore, Vano et al 5 found that a lower socioeconomic stratum had an adverse effect on the oral hygiene habits of Italian adults among the general population. Retired participants, homemakers and students showed better oral hygiene habits in the GPS group regarding both factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal diseases are among the most common oral pathologies, have multifactorial etiology, are characterized by numerous risk factors and can affect all populations throughout life [18], being related to poor oral hygiene [1].…”
Section: Discussionmentioning
confidence: 99%